10th Anniversary of Nanomaterials-Recent Advances in Environmental Nanoscience and Nanotechnology - Yentekakis, Ioannis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint contains contributions focusing on recent developments in the design, synthesis, and characterization of nanocatalysts intended for applications in environmental protection and low carbon footprint power generation processes thanks to the overall effort of scientists and researchers for a cleaner and more sustainable future. New synthetic approaches to the production and in-depth characterization of innovative nanostructured composites and hybrid materials with well-controlled textural and surface chemistry properties that give performance advantages in a variety of important environmental and energy applications such as CO2 utilization/recycling, hydrogen and syngas production, biosensing, and biocatalysis as well as in ways to obtain useful materials from waste are included, among others. This reprint is the result of one of the cutting-edge Special Issues in the field of Nanoscience and Nanotechnology organized by Nanomaterials to celebrate its 10th anniversary.